Thermo-structural analysis of the brazilian 14-x hypersonic aerospace vehicle - Felipe Jean da Costa (2014)
The use of computational tools in the aerospace industry has been an important ally in the prediction of physical phenomena. Investment in knowledge in computational simulation is essential for engineering professionals, who work in multidisciplinary design. However, paraphrasing the noble patron of aeronautics, Alberto Santos Dumont, "things are more beautiful when we have a wide vision of your work field", indicating, in the computational simulation context, that the knowledge of methods and theories allocated inside of the software black box allows a complete and lucid analysis of results. Evidently, by commercial reasons we cannot get the knowledge of how to give the total operation of the software, but the core concepts that guarantee the reliability of that can be studied. The Brazilian VHA 14-X is a technological demonstrator of a hypersonic airbreathing propulsion system based on supersonic combustion (scramjet) to fly at Earth';s atmosphere at 30 km altitude at Mach number 7 to 10, designed at the Laboratory of Aerothermodynamics and Hypersonics Prof. Henry T. Nagamatsu, at the Institute for Advanced Studies. Basically, scramjet is a fully integrated airbreathing aeronautical engine that uses the oblique/conical shock waves generated during the hypersonic flight, to promote compression and deceleration of freestream atmospheric air at the inlet of the scramjet. Scramjet is an aeronautical engine, without moving parts, therefore it is necessary another propulsion system to accelerate the scramjet to the operation conditions. The Brazilian two-stage rocket engines (S31 and S30) are able to boost the VHA 14-X to the predetermined conditions of the scramjet operation, 30 km altitude but at Mach number 7 and 10. Therefore, it is needed to design the structure of the VHA 14-X to support the aerodynamic loads during the atmospheric hypersonic flight at the same conditions. One-dimensional theoretical analysis, applied at 30 km altitude at Mach number 7 and 10, provide the pressure distribution on the VHA 14-X upper and lower surfaces. Structural materials for the stringers and ribs as well as coating materials for the thermal protection systems were specified based on preliminary studies. ANSYS Workbench software, which provides the Structural Numerical Analysis using Finite Element Method, has been applied to the structural analysis of the VHA 14-X waverider unpowered scramjet at 30 km altitude at Mach number 7 and 10. Stress field, strains and deformations are presented. Finally, the thermal response in terms of temperature field, total heat flux and directional heat flux in x, y and z axis are provided over the VHA 14-X waverider unpowered scramjet at 30 km altitude at Mach number 7 and 10.